2018
DOI: 10.11002/kjfp.2018.25.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and digestion enzyme inhibitory activity of Ganoderma lucidum depends on the extraction solvent

Abstract: This study investigated the nutritional properties and biological activities of Ganoderma lucidum (GL). The round type of GL contained higher carbohydrate content, while the Nokgak type of GL contained higher crude ash, crude fat, and crude protein content. The most abundant amino acid, fatty acid, mineral, and soluble vitamin observed were valine (round type: 11.90 mg/g and Nokgak type: 17.18 mg/g), linoleic acid (round type: 47.56% and Nokgak type: 75.68%), potassium (round type: 116.50 mg/100 g and Nokgak t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Chen et al [ 39 ] investigated the amylase and glucosidase inhibitory effects of five Ganoderma species and their triterpenoids, and G. lucidum triterpenes demonstrated the strongest inhibitory effect with the lowest IC 50 values. Similar results of isolated compounds from the members of Ganoderma were also reported by several authors [ 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 90%
“…Chen et al [ 39 ] investigated the amylase and glucosidase inhibitory effects of five Ganoderma species and their triterpenoids, and G. lucidum triterpenes demonstrated the strongest inhibitory effect with the lowest IC 50 values. Similar results of isolated compounds from the members of Ganoderma were also reported by several authors [ 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 90%
“…The fermentation broth of Reishi showed exceptional antidiabetic potential, considering that it inhibited the activity of α-amylase by as much as 78%. 51 Moreover, Reishi extract has also been shown to be very effective at inhibiting α-glucosidase in the study of Joo et al , 52 who reported an inhibition extent of 89.68%.…”
Section: Discussionmentioning
confidence: 99%
“…GL was extracted according to a previous study [ 12 ]. Dried GL was produced by Imsil Lingzi mushroom farming association corporation (Jeonbuk, Korea).…”
Section: Methodsmentioning
confidence: 99%